Progress in surface and membrane science. - Cadenhead, David Allan; Danielli, J. F. (James Frederic), 1911-1984 (Academic Press, 1976)
Progress in Surface and Membrane Science, Volume 11 covers the advances in the study of surface and membrane science. The book discusses the quantum theory of surface phenomena; some fundamental aspects of electrocrystallization; and exoelectric emission. The text also describes the surface of titanium dioxide; and the prospects for atomic resolution electron microscopy in membranology. Chemists, physicists, and people involved in the electrochemical power laboratory will find the book useful.